Review of impedance source power converter for electrical applications - M. A. K. Borelessa; K. T. M. U. Hemapala; V. Saravanan; K. M. Venkatachalam; M. Arumugam (Institute of Advanced Engineering and Science, 2021)
Power electronic converters have been actively researched and developed over the past decades. There is a growing need for new solutions and topography to increase the reliability and efficiency of alternatives with lower cost, size and weight. Resistor source converter is one of the most important power electronic converters that can be used for AC-DC, AC-AC, DC-DC and DC-DC converters which can be used for various applications such as photovoltaic systems, wind power systems, electricity. Vehicles and fuel cell applications. This article provides a comprehensive overview of Z-source converters and their implementation with new configurations with advanced features, emerging control strategies and applications.